Breast reconstruction in patients with BRCA mutation and breast cancer - our approach - Ventruba, Tomáš; Brančíková, Dagmar; Ventruba, Pavel; Minář, Luboš; Felsinger, Michal; Vomela, Jindřich (Ceska gynekologie, 2021)
OBJECTIVE: Analysis of our approach to breast reconstruction after mastectomy in women with breast cancer and/or BRCA mutations. Oncoplastic surgery enables procedures that are sufficiently radical and with a very good cosmetic effect. With the development of genetic testing programs, the need for prophylactic procedures is also increasing. One-sided curative performance and at the same time prophylactic surgery on the other breast can be used. METHODS: We use the possibility of immediate breast reconstruction simultaneously with subcutaneous and skin-saving mastectomy. We solve the reconstruction either with an expander and in the second time by inserting a silicone implant, or directly by inserting the implant alone or in combination with the use of autologous tissue, depending on further oncological treatment (chemotherapy or radiotherapy). RESULTS: One-hundred and three reconstructive surgeries were performed on 58 women with breast cancer and/or BRCA mutations from April 2017 to May 2020. Of these, there were 52 immediate reconstructions for untreated tumors. A tissue expander was inserted in 27 women (46.6% of the group) with locally advanced tumors and the need for subsequent radiotherapy (18 immediate and 9 delayed reconstructions). Breast implants were used in 52 women (89.7% of the group) in a total of 80 implants. Breast reconstruction of own tissues was performed in 8 women, of which 5 operations had immediate reconstruction. Postoperative complications occurred in 11 women and 15 corrective procedures were performed (12.7% of operations). CONCLUSION: Breast reconstruction is a comprehensive set of techniques by which any patient can obtain a breast so that it does not depend on the epithelium. Patients with locally advanced disease who receive neoadjuvant chemotherapy and radiotherapy are at greater risk of complications. With the growing number of breast cancers, the demand for reconstructive procedures, especially immediate reconstructions, is increasing.
Keywords: mutace; tissue lobe; nádory prsu; Mammaplasty; Female; breast cancer; Mastectomy; ženské pohlaví; mastectomy; lidé; Breast Neoplasms; pooperační komplikace; Mutation; expander; delayed reconstruction; breast implants; BRCA mutations; retrospektivní studie; Breast Implants; Postoperative Complications; mastektomie; prsní implantáty; immediate breast reconstruction; Retrospective Studies; mamoplastika; Humans